Using information and mobile technology improved elderly home care services. Issue 2 (June 2016) - Kuo, Mu-Hsing; Wang, Shu-Lin; Chen, Wei-Tu
Abstract: Background: Many international studies recognized that home care services for elderly can reduce a health system׳s financial burden while maintaining high quality standards of patient care. Nevertheless, published research also reports that first-line care or in-charge nurses often face many challenges while delivering the home care services. To deal with the challenges, researchers have suggested applying information and mobile communication technology (IMCT) to enhance the utilization of elderly home care services. Methods: We used a Service Oriented Architecture (SOA) to design the system structure and applied an IMCT to develop a mobile roaming sessions of the home care management system to help first-line nurses efficiently deliver care services while implementing functionality. The system includes three main modules: work scheduling, care service, and patient management. The work scheduling module used genetic algorithms to automatically generate monthly work schedules for nurses. Finally, we interviewed several users to understand the system usability. Results: We conducted a user experience interview to document and analyze the feasibility and efficiency of the system. The results showed that users found the system very useful in improving the home care services. Particularly, the care scheduling, care management, tour planning, and service logging functions are the most useful features of IMCT tools for improving the home care services. However, the small mobile phone screen and function integrations were main constraints in the system usability. Conclusions: We applied IMCT to develop a mobile roaming sessions of home care management system to help first-line nurses efficiently deliver care service. The SOA approach successfully allowed us to combine existing information applications in a hospital to the ad hoc reporting in a home care management system. The system cost effectively improved elderly care services for small- to medium-sized home care centers. Highlights: We reviewed international studies to recognize information technology requirements for home care services for elderly. We developed a mobile roaming sessions of the home care management system to help first-line nurses efficiently deliver care services. We conducted a user experience interview to document and analyze the feasibility of the system.